2004
DOI: 10.1093/carcin/bgh134
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution analysis of DNA copy number alterations in colorectal cancer by array-based comparative genomic hybridization

Abstract: Array-based comparative genomic hybridization (CGH) allows for the simultaneous examination of thousands of genomic loci at 1-2 Mb resolution. Copy number alterations detected by array-based CGH can aid in the identification and localization of cancer causing genes. Here we report the results of array-based CGH in a set of 125 primary colorectal tumors hybridized onto an array consisting of 2463 bacterial artificial chromosome clones. On average, 17.3% of the entire genome was altered in our samples (8.5 +/- 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
146
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(178 citation statements)
references
References 51 publications
(45 reference statements)
29
146
3
Order By: Relevance
“…Davidson et al, 2000;AbdelRahman et al, 2001;Karan et al, 2003;Hurst et al, 2004;Hwang et al, 2004), and more recently array CGH has begun to provide more detail of these losses (e.g. Paris et al, 2003;Douglas et al, 2004;Hurst et al, 2004;Nakao et al, 2004;Garcia et al, 2005). Distal 8p also frequently shows loss of heterozygosity (LOH), which would often reflect loss through unbalanced translocation (for references see Adams et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Davidson et al, 2000;AbdelRahman et al, 2001;Karan et al, 2003;Hurst et al, 2004;Hwang et al, 2004), and more recently array CGH has begun to provide more detail of these losses (e.g. Paris et al, 2003;Douglas et al, 2004;Hurst et al, 2004;Nakao et al, 2004;Garcia et al, 2005). Distal 8p also frequently shows loss of heterozygosity (LOH), which would often reflect loss through unbalanced translocation (for references see Adams et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The long-suspected amplification target, FGFR1, was excluded from the current consensus amplicon and detected as amplified in fewer, 10-15%, of cases (Theillet et al, 1993;Ugolini et al, 1999;Prentice et al, 2005). Amplification of proximal 8p is also seen in other carcinomas (Veltman et al, 2003;Nakao et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these genetic aberrations occurred in regions reported to be associated with colorectal cancer. 23,24 These changes include amplifications on chromosome 20q, 13 and 8q, and copy number loss on the long arm of chromosome 18 and on chromosome 8p. [24][25][26][27][28] Both aberrant specimens showed amplifications of entire chromosomes: 7, 13 and 16, as well as partially overlapping aberrations on chromosome 20 (Figure 4a).…”
Section: Validation For Downstream High-throughput Technologiesmentioning
confidence: 99%
“…For each probe, the fraction of tumors with gains and losses over the Nakao et al (2004) Example of informative genomic regions for 37 colorectal cancers from Douglas et al (2004). Genome alterations already reported by Douglas et al (2004) were identified by our software (alterations are represented by vertical bandings ranging from dark to light pink for gain regions, dark to light green for loss regions and blue for amplified regions -amplicons are arbitrarily defined here as regions with log 2 -ratio>2).…”
Section: Meta-analysis Examplesmentioning
confidence: 99%
“…Many studies have been carried out on bladder cancer (Veltman et al, 2003;Blaveri et al, 2005;Stransky et al, 2006), brain cancer (Bredel et al, 2005;Kotliarov et al, 2006), breast cancer (Pollack et al, 2002;Fridlyand et al, 2006), colon cancer (Douglas et al, 2004;Nakao et al, 2004), liver cancer (Patil et al, 2005), lymphoma (de Leeuw et al, 2004), neuroblastoma (JanoueixLerosey et al, 2005;Mosse et al, 2005), mouth cancer (Snijders et al, 2005), pancreas cancer (Gysin et al, 2005) and replication timing (Woodfine et al, 2004;Janoueix-Lerosey et al, 2005). Comparisons of the results of experiments from different laboratories, on different types of cancer, are required to validate results or hypotheses and to improve our understanding of the recurrent alterations involved in cancer.…”
Section: Introductionmentioning
confidence: 99%